Condições de vida e trabalho de imigrantes haitianos residentes no município de Cascavel/Paraná - David, Jean Bart (2021)
In the West of Paraná, haitians began to arrive in 2010, brought by local businessmen and by the abundance of job offers, especially in slaughterhouses for pigs and poultry. The migratory wave of Haitians to Brazil creates new challenges for public policies aimed at ensuring fundamental rights in the country. Considering these factors, the general objective of this research is to analyze the ways of life and work of Haitian immigrants living in the municipality of Cascavel / Paraná and their relationship with the health-disease process. the research is characterized as exploratory and descriptive with a quantitative approach. The concept of social determination was used as the conceptual theoretical framework of the present research. Data collection was carried out through the application of semi-structured interviews with Haitian immigrants. Data collection was carried out through the application of semi-structured interviews with Haitian immigrants. 128 participants were interviewed between December 2019 to January 2020 and July 2020 to December 2020. The results show a predominantly male population 75,0% (n = 96), young adults 71,0% (n = 91), speak two languages or more 87,5% (n = 112), of Catholic religion 61,7% (n = 79), with high school education or above 57,0% (n = 73), with 57,8% (n = 74) arriving in Brazil between the years 2015 and 2017 in search of work. Of the interviewees, the majority, 82,0% (n = 105), were employed and occupying positions in refrigerators 72,4% (n = 76) and in construction 16,2% (n = 17), but 18,0% (n = 23) were unemployed at the time of the field research. Among those with jobs, 91,4% (n = 96) are formally employed and 8,6% (n = 9) are self-employed (small businesses). Of those who are employed, the income is of a minimum wage for 92,4% (n = 97), characterizing a life of consumption quite austere, both for the low wages, as for the necessity of remittance of values for the relatives that remain in Haiti, in this condition are 25,8% (n = 33) of the interviewees who send 40,0% of their monthly income to their country of origin. Regarding ideological and organizational life, highlights for leisure activities, 57,8% (n = 74) opted for television, 28,9% (n = 37) for meetings between friends and another 13,2 % (17) for music. Other observations, 2,3% (n = 3) declared having access to education and 90,6% (n = 116) mentioned access to public health. Self-organization creates support and solidarity networks to face the difficulties of the immigration process. It is concluded that favoring the arrival of Haitian immigrants to work in slaughterhouses in the region, may indicate exploitation of the work of vulnerable groups economically and socially. Integration policies and the recognition of school education in the country of origin can contribute to improving the living conditions of this population in our country.